Pengaruh Diameter Katoda pada Sensitivitas Pengukuran Gradien Kecepatan dengan Metode Polarografi - Sukamta Sukamta (Universitas Muhammadiyah Yogyakarta, 2008)
Wall velocity gradient measurement using polarography gives very accurate output due to the absence of problem in fluid flow. Therefore this experiment is highly recommended. Based on the polarogram resulted in the polarography method, the potential that has to be applied to both electrode is 0.25 – 0.75 Volt, whilst in the experiment 0.45 is applied. Calibration has been done to single phase flow, by measuring as a result of by friction between wall and current flow through electrode at constant flow rate. The ΔP data are used to determine τ. Relation plot between τ (resulted from ΔP measurement) and current can be obtained from the data acquisition device. The result of this research shows that the value of wall shear stress (as velocity gradient) is influenced by the increase of flow rate. Whilst measurement of wall shear stress shows that the cathode area gives effect on the sensitivity of the measurement, a small cathode results in better shear stress data measurement (more sensitive). In this research the best wall shear stress was resulted in cathode with diameter d=0.2 mm.